Lead and bismuth abrasion resistant protective coating and preparation method thereof
By designing the periodic cyclic gradient structure coatings of CrN phase, Cr2N phase and Cr phase in the lead-bismuth eutectic alloy environment, the failure problem of traditional coatings in high stress environment is solved, and corrosion resistance under high temperature and high pressure is achieved. Improved wear resistance and is suitable for the protection of structural materials of the fourth generation nuclear reactor.
Patent Information
- Application Number
- CN202411875200.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-01-17
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional structural materials are prone to corrosion and wear in lead-bismuth eutectic alloy environments, and the brittleness of the ceramic coating does not match the soft metal substrate, resulting in failure under high stress environments.
Design a periodic cyclic gradient structure coating composed of CrN phase, Cr2N phase and Cr phase. By adjusting N2 gas flow and PVD technology, the microstructure optimization of the coating is achieved, the corrosion resistance and wear resistance are enhanced, and the corrosion resistance and wear resistance is enhanced in 316 stainless steel CrXN layers are deposited on the surface to improve elastoplastic matching.
It significantly improves the failure resistance of the coating in high temperature and high pressure environments, overcomes the brittleness of ceramic materials, enhances the comprehensive performance, meets the strict requirements of the nuclear industry for material durability, and reduces wear rate and maintenance costs.
Smart Images

Figure CN119320933A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of protective coatings, in particular to a protective coating resistant to lead-bismuth abrasion and a preparation method thereof. Background Art
[0002] Lead-bismuth eutectic alloy (LBE), a liquid heavy metal, is a candidate primary coolant and sputtering target for fast neutron reactor design due to its excellent neutron, hydrothermal and thermophysical properties. It has been selected as one of the six reactor concepts in the fourth generation (Gen-IV) technology roadmap. At the same time, LBE has a high boiling point (>1600°C, higher than the melting point of steel) and does not react strongly with air or water, thus simplifying the nuclear reactor structure and preventing many types of accidents inherent in other reactor designs, giving the fourth generation liquid LBE reactor inherent safety. However, in order to ensure the safe and stable operation of the fourth generation nuclear reactor, higher requirements are also placed on the structural materials in the reactor. The reason is that LBE has a high solubility for some major elements in traditional structural materials, causing traditional structural materials to corrode rapidly in the LBE environment and then fail. At the same time, the circulation of heavy metal LBE on the surface of structural materials also causes wear to the structural materials. Materials peeled off from other components in the pile may also join the friction system between LBE and structural materials as abrasives, thus forming a friction environment for abrasive wear and further accelerating the failure of structural materials.
[0003] In this case, the scientific community proposed to deposit a dense coating on the surface of existing structural materials as a barrier to protect the substrate from LBE corrosion and wear. CrN phase ceramic coating is an ideal candidate coating material because of its inertness to LBE, excellent radiation resistance and high temperature stability, high hardness and mature preparation process. However, the inherent brittleness of ceramic materials makes them mismatched with the elastic-plastic properties of soft metals, and they are prone to failure in high stress environments. Based on this, the present invention designs a new coating structure, which effectively improves the elastic-plastic matching between the CrN coating and the soft metal substrate, while maintaining high hardness, high wear resistance and LBE corrosion resistance. Summary of the invention
[0004] The purpose of the present invention is to meet the performance requirements of lead-bismuth corrosion resistance, wear and high strength of the surface coating of structural materials in the fourth-generation reactor, and to design and prepare a coating structure and a preparation method of a cyclic gradient structure that interrupts the continuous growth of columnar crystals and effectively increases the free surface volume fraction in the ceramic layer. To this end, a protective coating resistant to lead-bismuth abrasion and a preparation method thereof are provided to solve the problems raised in the above-mentioned background technology.
[0005] To achieve the above object, the present invention provides the following technical solution: a protective coating resistant to lead-bismuth abrasion, comprising a periodic cyclic gradient structure coating composed of CrN phase, Cr2N phase and Cr phase obtained by periodically and continuously changing the N2 gas flow rate, wherein the bottom layer of the periodic cyclic gradient structure coating is a Cr layer, and the middle layer is a Cr layer. X N layer, the top layer is CrN layer, Cr X The N layer includes 45-99% Cr and 50-55% N. X The thickness of N is in the range of 0.2 to 0.4 μm (optimal at 0.3 μm), and the thickness of Cr is in the range of 0.05 to 0.2 μm (optimal at 0.1 μm). PVD technology is used to deposit Cr on the surface of 316 stainless steel. X When N is low, the flow rate of Ar gas is controlled in the range of 40sccm to 50sccm, and the flow rate of nitrogen gas is controlled in the range of 1sccm to 50sccm. In the PVD process, a gas mixer is used to mix the working gas and the reaction gas in advance and then inject them into the cavity. In this unique coating structure, the microstructure of the coating is optimized through sophisticated gas flow regulation and PVD technology, which effectively enhances the corrosion resistance and wear resistance of the coating. In addition, while maintaining its hardness, the coating's elastic-plastic properties are better matched with the soft metal substrate, significantly improving the coating's ability to resist failure in high temperature and high pressure environments. The successful development of this coating structure not only overcomes the inherent brittleness of ceramic materials, but also greatly improves the comprehensive performance of the coating in practical applications, meeting the nuclear industry's strict requirements for the durability of materials in extreme environments.
[0006] Another technical problem to be solved by the present invention is to provide a method for preparing a protective coating resistant to lead-bismuth abrasion, the method comprising the following steps: Step 1: First, place the 316 stainless steel substrate in an Ar gas environment, 60mm to 150mm away from the target surface, and keep the substrate rotating in front of the target or rotating in the furnace; adjust the vacuum degree to 0.1 to 2Pa (1.2Pa is optimal) by adjusting the Ar gas flow rate; perform glow cleaning in a vacuum coating equipment under bias conditions of -300V to -1000V (-800V is optimal) and a duty cycle of 60% to 90% (90% is optimal) for 20 to 60 minutes (40 minutes is optimal); Step 2: After the glow cleaning is completed, adjust the pulse bias voltage to -50V to -300V (-150V is optimal), the duty cycle is 60% to 90% (90% is optimal), and start to deposit the Cr coating. Thereafter, the bias voltage, duty cycle and target current remain unchanged. After the glow cleaning of the substrate surface is completed, a Cr layer is deposited on the substrate surface by PVD method. The substrate is placed in an Ar gas environment, the vacuum degree is 0.25 to 1.0Pa (0.3Pa is optimal), the pulse bias voltage is -50 to -200V (-150V is optimal), and the duty cycle is 40% to 90% (90% is optimal). Under the conditions, turn on the Cr target, adjust the average target current to 0.5 to 20A (15A is optimal), and deposit a Cr layer on the substrate surface. The deposition thickness is 0.05 to 0.2μm and is adjusted according to the corresponding deposition time; Step 3: After the Cr layer is deposited on the substrate surface, the Cr target and bias power supply parameters are kept unchanged, and N2 gas is introduced while Ar gas is introduced. The N2 gas flow rate is adjusted by the flow meter from 0 sccm to 50 sccm. When it reaches 50 sccm, it stays for 30s to 60s to deposit the CrN layer. After that, the N2 gas flow rate is decreased from 50 sccm to 0 sccm, and the flow rate change frequency is kept consistent with the increase. Then, the Cr layer is deposited, and the above steps are repeated periodically to deposit the cyclic gradient Cr. X N coating, the outermost layer is CrN layer, in order to improve the ability of the coating to resist lead-bismuth corrosion, the frequency of N2 gas flow adjustment is determined according to the deposition rate, so that the operation can form Cr between the Cr layer and the CrN layer. X N transition layer, refines the grain size of the ceramic layer, increases the free surface volume fraction in the ceramic layer, and the high volume fraction of the ceramic phase and the high volume fraction of the free surface area improve the strength and wear resistance of the coating. X N is relatively inert to LBE and can effectively protect the substrate from corrosion.
[0007] Preferably, the workpiece is sputter-coated using PVD technology, and vacuuming (better than 5E-6Torr), heating (200 degrees Celsius-500 degrees Celsius), plasma cleaning (using Ar ions to remove the oxide layer on the surface of the workpiece and enhance the adhesion of the film layer) and sputtering deposition of a periodic cyclic gradient structure coating are performed in sequence.
[0008] The present invention provides a protective coating resistant to lead-bismuth abrasion and a preparation method thereof, which has the following beneficial effects: (1) The present invention utilizes the characteristics of CrN ceramic coating having two phases, Cr2N and CrN, and obtains a ceramic phase with a layered structure and a high volume fraction by reasonably adjusting the flow rate of N2 gas during the preparation process. The structure retains high toughness and high hardness at the same time, thereby achieving excellent performance in the field of surface protection against high-temperature lead-bismuth corrosion.
[0009] (2) The present invention utilizes the inertness of CrN ceramics to LBE and utilizes Cr X N has the characteristics of Cr2N phase and CrN phase. By periodically changing the flow rate of N2 gas into the magnetron sputtering chamber, a coating with a layered structure and a high volume fraction of ceramic phase is obtained. The high proportion of free surface in the ceramic phase of the coating is activated at high temperature, and then it can be well matched with the soft metal substrate such as 316 stainless steel in elastic-plastic properties, thereby improving the coating's ability to resist liquid LBE abrasion.
[0010] (3) Compared with the traditional multilayer structure, the coating structure designed by the invention retains the high hardness characteristics of the ceramic phase. At the same time, due to the optimization of the structure, the mechanical properties of the coating in high temperature environment are significantly improved, especially in reducing the wear rate. This feature makes the invention have broad application prospects under extreme working conditions and helps to improve the service life and reliability of the material. In addition, the excellent performance of LBE corrosion resistance further broadens its application potential in the nuclear industry and other fields.
[0011] (4) Compared with the traditional CrN single-phase ceramic layer, the coating structure designed by this invention has more free surface and thin tough metal phase layer, which improves the toughness of the coating. This not only reduces the wear rate in high-temperature wear tests, but also improves the coating's ability to resist fracture in complex stress environments. At the same time, this design makes the coating show extremely high stability in liquid LBE corrosion tests, which is conducive to reducing maintenance costs and improving equipment operation efficiency.
[0012] (5) The coating structure of the invention is very simple and efficient to prepare. The entire deposition process can be completed by simply setting up a flow controller. In addition, the simple preparation process of the coating greatly reduces production costs and shortens production cycles, making it more competitive in large-scale industrial applications. In the liquid LBE corrosion test, the coating exhibited excellent performance, further verifying its applicability in extreme environments, making it more durable and stable than other materials under harsh working conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 It is a schematic diagram of the coating structure of the present invention; Figure 2 XRD phase diagrams of Example 1, Example 2, Comparative Example 1 and Comparative Example 2 of the present invention; Figure 3 Surface and cross-sectional SEM images of Example 1, Example 2, Comparative Example 1 and Comparative Example 2 of the present invention; Figure 4 The nanohardness display diagrams of Example 1, Example 2, Comparative Example 1 and Comparative Example 2 of the present invention; Figure 5The wear rate diagram calculated after wear of the present invention; Figure 6 This is the interface morphology of the coating of the present invention. DETAILED DESCRIPTION
[0014] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0015] Examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.
[0016] Embodiment 1: After pretreatment, the 316 substrate was placed in front of the magnetron target, 80 mm from the target surface, so that it rotated in front of the target. The vacuum was evacuated to a background vacuum of less than 1.0*10-3Pa, and then Ar gas was filled to a vacuum of 1.2Pa. The pulse bias was turned on, and the parameters were set to -800V, and the duty cycle was 90% for glow cleaning for 40 minutes. After the glow cleaning was completed, the gas pressure was adjusted to 0.3Pa by changing the Ar gas flow rate, and the bias was adjusted to -150V. Other parameters remained unchanged, the Cr target was turned on, a DC power supply was applied to the target surface, and the target current was adjusted to 15A. The Cr layer was deposited for 5 minutes with a thickness of 100nm.
[0017] Then nitrogen was introduced to deposit Cr X N phase layer; the automatic adjustment system automatically increases the N2 gas flow rate by 1 sccm every 30 seconds. To maintain the gas pressure at 0.3 Pa, the Ar gas flow rate is reduced accordingly until the N2 gas flow rate increases to 50 sccm, and the gradient Cr is obtained. X N structure, and then continue sputtering for 2 minutes to obtain a CrN layer. Then reduce the N2 gas by 1 point every 40 seconds until the N2 flow rate is 0. This process is one cycle, and then continue to repeat the above process for 10 cycles to obtain the target coating, with the top layer being a CrN layer. The deposited coating thickness is 3.4μm.
[0018] Embodiment 2: The deposited Cr X The preparation method of N cycle gradient coating comprises the following steps: The whole preparation process is as shown in Example 1, except that the gradient Cr is deposited XDuring the N coating process, the N2 gas flow rate was changed by 1 sccm every 20 s to obtain a cyclic gradient Cr with the same thickness but 40 cycles. X N coating.
[0019] Comparative Example 1: The pre-treated substrate was cleaned using the same glow cleaning technology as in Examples 1 and 2. Then, 50 sccm Ar gas and 50 sccm N2 gas were introduced, the gas pressure was adjusted to 0.3 Pa through the grating valve, the bias voltage was adjusted to -150 V, other parameters remained unchanged, the Cr target was turned on, a DC power supply was applied to the target surface, the target current was adjusted to 15 A, and the CrN coating was deposited for 100 min to obtain a 3.4 μm thick CrN coating.
[0020] Comparative Example 2: The pre-treated substrate was cleaned using the same glow cleaning technology as in Examples 1 and 2. Then, 80 sccm Ar gas was introduced, the gas pressure was adjusted to 0.3 Pa through the grating, the bias voltage was adjusted to -150 V, other parameters remained unchanged, the Cr target was turned on, a DC power supply was applied to the target surface, the target current was adjusted to 15 A, and the Cr coating was deposited for 5 minutes to obtain a 200 nm thick Cr layer, and then 50 sccm N2 gas was introduced for deposition, and the Ar gas flow was adjusted to 50 sccm to deposit a CrN layer for 5 minutes. The above Cr layer and CrN layer are a periodic layer, and the above steps are continued for 10 cycles of co-deposition, the top layer is the CrN layer, and a periodic multilayer Cr / CrN coating is obtained with a thickness of 3.4 μm.
[0021] The schematic diagram of the coating structure of the present invention is as follows Figure 1 As shown, the thickness of the metal Cr layer is 60-120nm (preferably 80nm) to increase the overall toughness of the coating. When the coating is subjected to an external load, the overall structure of the coating can be kept intact to resist the invasion of LBE corrosion. X The thickness of the N layer is 250-530nm (preferably 300nm), which is inert to LBE and can well protect the coating from LBE erosion, while increasing the hardness of the coating and maintaining good mechanical properties such as wear resistance; The XRD phases of Example 1, Example 2, Comparative Example 1 and Comparative Example 2 are as follows: Figure 2 As shown, it can be found that both Example 1 and Example 2 have three phases of Cr, Cr2N and CrN, while Comparative Example 1 has only CrN phase, confirming that a CrN single-phase coating is obtained, and Example 2 has two phases of CrN and Cr.
[0022] The surface and cross-sectional SEM images of Example 1, Example 2, Comparative Example 1 and Comparative Example 2 are as follows: Figure 3As shown, it can be found that the surface morphology of Example 1 shows that the grains are of different sizes, which is the result of competitive growth. In this competitive growth process, more free surfaces are obtained. Its cross-sectional morphology presents a typical layered structure; Example 2 has smaller grains, and the surface presents a cluster structure. The smaller single-layer period makes the cross-section present a large number of irregular bumps, which are all caused by the low thickness of a single period. Comparative Example 1 is a typical NaCl structure CrN, the grains are in the shape of a "ridge", and the cross-section also shows a vertically grown columnar crystal structure. The grains of Comparative Example 2 are finer, and the shape and size are more consistent. The cross-sectional morphology shows a single-layer columnar crystal structure.
[0023] The nanohardness of Example 1, Example 2, Comparative Example 1 and Comparative Example 2 is Figure 4 Among them, Comparative Example 1 has the highest hardness due to the single-phase CrN coating, while the multilayer structure of Comparative Example 2 has the lowest hardness due to the higher soft metal phase. Since the volume fraction of the ceramic phase of Example 1 and Example 2 is between that of Comparative Example 1 and Comparative Example 2, the hardness is also between them, but Example 2 still retains a high hardness due to the presence of a large number of phase interfaces to harden the coating, which is close to Comparative Example 1 of the single-phase ceramic coating.
[0024] High temperature mechanical properties: The high temperature wear test of Example 1, Example 2, Comparative Example 1 and Comparative Example 2 was carried out on the equipment MST-3001, using Al2O3 balls as the grinding balls, the temperature was 500°C, the normal load was 2N, 300r / min, and the wear time was 40min. The wear rate was calculated after wear (such as Figure 5 ), Example 1 has the lowest wear rate, while Comparative Example 1 has the highest wear rate. This is because in a high temperature environment, more free surfaces can obtain better plastic deformation space, and the elastic modulus of the substrate is lower. Under a force of 2N, better elastic modulus matching and higher hardness are the main reasons for reducing the wear rate of Example 1.
[0025] Example 1 LBE corrosion resistance: Liquid LBE corrosion test was carried out under the conditions of corrosion temperature 500°C, O element content 1´10-7wt.%, and corrosion time 500 hours. The coating interface morphology is as follows Figure 6 The cross-sectional morphology of the sample after corrosion and the EDS signals of each element are shown as follows: (a) Cross-sectional morphology; (b) Cr; (c) N; (d) O; (e) Fe; (f) Pb; (g) Bi. From the morphology, the coating remains intact as a whole and is not damaged by corrosion. Pb and Bi elements do not invade the interior of the coating, and the coating effectively protects the substrate. Combined with the coating morphology, it can be judged that the interior of the coating is basically not oxidized.
[0026] Beneficial effects: 1. The coating structure designed by the invention retains the high hardness characteristics of the ceramic phase compared to the traditional multilayer structure. At the same time, due to the optimization of the structure, the mechanical properties of the coating in high temperature environments are significantly improved, especially in reducing the wear rate. This feature makes the invention have broad application prospects under extreme working conditions and helps to improve the service life and reliability of the material. In addition, the excellent performance of LBE corrosion resistance further broadens its application potential in the nuclear industry and other fields.
[0027] 2. The coating structure designed by this invention has more free surface and thin tough metal phase layer compared with the traditional CrN single-phase ceramic layer, which improves the toughness of the coating. This not only reduces the wear rate in high-temperature wear tests, but also improves the coating's ability to resist fracture in complex stress environments. At the same time, this design makes the coating show extremely high stability in liquid LBE corrosion tests, which is conducive to reducing maintenance costs and improving equipment operation efficiency.
[0028] 3. The coating structure of the invention is very simple and efficient to prepare. The entire deposition process can be completed by simply setting up a flow controller. In addition, the simple preparation process of the coating greatly reduces production costs and shortens production cycles, making it more competitive in large-scale industrial applications. In the liquid LBE corrosion test, the coating exhibited excellent performance, further verifying its applicability in extreme environments, making it more durable and stable than other materials under harsh working conditions.
[0029] In summary, the cyclic gradient structure coating designed in the present invention has the characteristics of high toughness of the multilayer structure and high hardness of the ceramic coating. By increasing the free surface area in the ceramic coating, higher strength and high-temperature wear resistance are obtained. The LBE inertness of CrN itself enables it to be used for surface protection of structural materials in lead-bismuth piles.
[0030] The present invention can also be used in complex working conditions with impact loads, friction and wear, corrosive fluids, and high temperatures, such as machining fields such as mold steel, cutting tools, and micro-molding molds. At the same time, the coating can still maintain its structural stability and protective performance when dealing with extreme temperature changes, effectively extending the service life of the equipment and reducing the frequency of maintenance.
[0031] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0032] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A protective coating resistant to lead-bismuth abrasion, comprising a periodic cyclic gradient structure coating composed of CrN phase, Cr2N phase and Cr phase obtained by periodically and continuously changing the N2 gas flow rate, characterized in that: The bottom layer of the periodic cyclic gradient structure coating is a Cr layer, and the middle layer is a Cr X N layer, the top layer is CrN layer, Cr X The N layer contains 45-99% Cr and 50-55% N. X The thickness of the N layer ranges from 0.2 to 0.4 μm, and the thickness of the Cr layer ranges from 0.05 to 0.2 μm.
2. A method for preparing a protective coating resistant to lead-bismuth abrasion as claimed in claim 1, characterized in that: The method comprises the following steps: Step 1: Place the 316 stainless steel substrate in an Ar gas environment, 60mm to 150mm away from the target surface, and keep the substrate rotating in front of the target or rotating in the furnace; Step 2: After the glow cleaning is completed, the pulse bias voltage is adjusted to -50V to -300V, the duty cycle is 60% to 90%, and the Cr coating is deposited. Thereafter, the bias voltage, duty cycle and target current remain unchanged. After the glow cleaning of the substrate surface is completed, the Cr layer is deposited on the substrate surface by PVD method. Step 3: After the Cr layer is deposited on the substrate surface, the Cr target and bias power supply parameters are kept unchanged, and N2 gas is introduced while Ar gas is introduced. The N2 gas flow rate is adjusted by the flow meter from 0 sccm to 50 sccm. When it reaches 50 sccm, it stays for 30s to 60s to deposit the CrN layer. After that, the N2 gas flow rate is decreased from 50 sccm to 0 sccm, and the flow rate change frequency is kept consistent with the increase. Then, the Cr layer is deposited, and the above steps are repeated periodically to deposit the cyclic gradient Cr. X N coating, the outermost layer is CrN layer, so as to improve the ability of the coating to resist lead-bismuth corrosion.
3. The method for preparing a protective coating resistant to lead-bismuth abrasion according to claim 2, characterized in that: The workpiece is sputter-coated using PVD technology, which sequentially performs vacuuming, heating, plasma cleaning, and sputtering deposition of a periodic cyclic gradient structure coating.
4. The method for preparing a protective coating resistant to lead-bismuth abrasion according to claim 2, characterized in that: In step 1, the vacuum degree is adjusted to 0.1-2 Pa by adjusting the Ar gas flow rate; glow cleaning is performed in the vacuum coating equipment under bias conditions of -300 V to -1000 V and a duty cycle of 60% to 90% for 20 to 60 minutes.
5. The method for preparing a protective coating resistant to lead-bismuth abrasion according to claim 2, characterized in that: In step 2, the substrate is placed in an Ar gas environment with a vacuum degree of 0.25 to 1.0 Pa, a pulse bias voltage of -50 to -200 V, and a duty cycle of 40% to 90%. The Cr target is turned on, the average current of the target is adjusted to 0.5 to 20 A, and a Cr layer is deposited on the surface of the substrate. The deposition thickness is 0.05 to 0.2 μm and is adjusted according to the corresponding deposition time.
6. The method for preparing a protective coating resistant to lead-bismuth abrasion according to claim 2, characterized in that: The frequency of N2 gas flow adjustment in step 3 is determined according to the deposition rate, so that Cr can be formed between the Cr layer and the CrN layer. X N transition layer, refines the grain size of the ceramic layer, increases the free surface volume fraction in the ceramic layer, and the high volume fraction of the ceramic phase and the high volume fraction of the free surface area improve the strength and wear resistance of the coating. X N is relatively inert to LBE and can effectively protect the substrate from corrosion.
Citation Information
Patent Citations
Composite coating on surface of valve sealing piece and preparation method for composite coating
CN103522627A
Preparation method of decorating protective coating for CrNx-based component gradient transition
CN103741108A
Low-stress high-wear-resisting erosion-resisting coating and preparing method and application
CN109666904A
Preparation method of metal-ceramic composite coating resistant to liquid lead / lead bismuth corrosion
CN115928018A
Pulse magnetron sputtering-based chromium nitride multilayer nano coating and preparation method thereof
CN116426887A